Choice of Law and Nazi-Looted Art Restitution: Cassirer v. Thyssen-Bornemisza Collection Foundation - Vastano, Julia (American Journal of Trade and Policy, 2022)
On April 21, 2022, the Supreme Court came to an unanimous decision in Cassirer v. Thyssen-Bornemisza Collection Foundation, a case concerning the legal ownership of a valuable painting by Camille Pissarro that was appropriated by the Nazi regime during the 1930s when its Jewish owners fled to the United States. After World War II, the painting changed ownership several times, ultimately to be acquired by Baron Hans Heinrich who sold it to the Thyssen-Bornemisza Collection Foundation in the Kingdom of Spain. After sixteen years of litigation and four appeals to the Ninth Circuit, the Supreme Court vacated and remanded the case back to the Ninth Circuit. The opinion, written by Justice Kagan, contended that in a suit raising non-federal claims against a foreign state or instrumentality under the FSIA, a court should determine the substantive law by using the same voice of law rule applicable in a similar suit against a private party. This paper will introduce the facts of Cassirer, present its procedural history, and dissect its treatment before the United States Supreme Court. This analysis will conclude with a discussion of the potential implications of the Cassirer decision on future Nazi-looted art claims.